EFL TEACHERS CHALLENGES IN DESIGNING ACCESSIBLE LEARNING TASKS - Mada, Syahban; Wahyuni B, Asti; Nur, Sahril (English Education Journal, 2024)
This study aims to identify the challenges faced by English as Foreign Language (EFL) teachers in creating tasks that are accessible to all learners. The subjects of this study are 28 EFL teachers who teach at various schools in South Sulawesi. This study uses a qualitative descriptive approach to deeply explore data through interviews, observations, and document analysis. The results show that the main challenges faced by teachers include differences in student proficiency levels, limited resources, and a lack of training in designing inclusive tasks. Additionally, factors such as the learning environment and technological barriers also affect teachers' ability to meet the needs of all learners. This study provides important insights for the development of more inclusive teaching strategies that support effective learning in EFL classrooms.